2015
DOI: 10.1371/journal.pone.0140670
|View full text |Cite
|
Sign up to set email alerts
|

Routes of Hendra Virus Excretion in Naturally-Infected Flying-Foxes: Implications for Viral Transmission and Spillover Risk

Abstract: Pteropid bats or flying-foxes (Chiroptera: Pteropodidae) are the natural host of Hendra virus (HeV) which sporadically causes fatal disease in horses and humans in eastern Australia. While there is strong evidence that urine is an important infectious medium that likely drives bat to bat transmission and bat to horse transmission, there is uncertainty about the relative importance of alternative routes of excretion such as nasal and oral secretions, and faeces. Identifying the potential routes of HeV excretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
109
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 43 publications
3
109
0
2
Order By: Relevance
“…HeV spills over to horses from two of the four Australian flying fox species (Smith et al 2014; Edson et al 2015; Martin et al 2016). We treated these species as two separate reservoir host systems (Smith et al 2014; Edson et al 2015; Martin et al 2018) that were geographically limited to the areas colonisable by P. alecto and P. conspicillatus (Soberón et al 2005; Martin et al 2016).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HeV spills over to horses from two of the four Australian flying fox species (Smith et al 2014; Edson et al 2015; Martin et al 2016). We treated these species as two separate reservoir host systems (Smith et al 2014; Edson et al 2015; Martin et al 2018) that were geographically limited to the areas colonisable by P. alecto and P. conspicillatus (Soberón et al 2005; Martin et al 2016).…”
Section: Methodsmentioning
confidence: 99%
“…Hendra virus (HeV, Paramyxoviridae: Henipavirus ) is another bat-borne virus that spills over into domestic animals, in its case horses, and then people with high case fatality rates of 50–75% (Halpin et al 2011; Smith et al 2014; Edson et al 2015; Martin et al 2016). It was discovered in 1994 in a Brisbane suburb in Queensland, Australia, with two of the four Australian mainland flying fox species, Pteropus alecto and P. conspicillatus , as its major reservoir hosts (Halpin et al 2011; Smith et al 2014; Edson et al 2015; Martin et al 2016), although antibodies against HeV are commonly found in P. scapulatus and P. poliocephalus (Young et al 1996; Plowright et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bat urine and faeces have been favoured as non-invasive samples for virus discovery, however active bat catching and sampling can give more accurate calculations of viral prevalence. In the case of Hendra virus, urine was the most significant form of virus transmission, with higher titres of virus seen in urine compared to specimens such as nasal swabs, faecal samples and serum 21 . Pooled urine can be collected from plastic sheets laid below bat colonies and stored in a viral transport medium at À808C for later analysis 22 .…”
Section: Ina L Smithmentioning
confidence: 99%
“…The spillover of Hendra virus (HeV) into horses, and subsequent transmission to humans, has resulted in fatal respiratory and neurological disease (Field et al., ; Playford et al., ). Australian flying‐foxes of the genus Pteropus are considered to be the reservoir host of HeV (Halpin et al., ; Field et al., ), with recent research demonstrating that Pteropus alecto and Pteropus conspicillatus are the predominant hosts of this virus (Smith et al., ; Edson et al., ; Goldspink et al., ). The most parsimonious hypotheses on the mode of HeV transmission, both between flying‐foxes, and from flying‐foxes to horses, propose direct or indirect contact with infected urine (Field et al., , ; Smith et al., ; Edson et al., ), although neither transmission cycle has been conclusively demonstrated.…”
Section: Introductionmentioning
confidence: 99%